Optoelectronics Materials and Devices - Pyshkin, Sergei L.; Ballato, John (IntechOpen, 2015)
Optoelectronics Materials and Devices follows the Optoelectronics Books II and III published in 2011 and 2013, as part of the InTech collection of international works on optoelectronics. Accordingly, as with the first two books of the collection, this book covers recent achievements by specialists around the world. The growing number of countries participating in this endeavor as well as joint participation of the US and Moldova scientists in this edition testifies to the unifying effect of science. An interested reader will find in the book the description of properties and applications employing organic and inorganic materials, as well as the methods of fabrication and analysis of operation and regions of application of modern optoelectronic devices.